2015
DOI: 10.1021/acs.jpca.5b02946
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Hydrated Monovalent First Row Transition Metal Ions [M(H2O)n]+, M = Cr, Mn, Fe, Co, Ni, Cu, and Zn, n < 50, Toward Acetonitrile

Abstract: Reactions of [M(H2O)n](+), M = Cr, Mn, Fe, Co, Ni, Cu, and Zn, n < 50, with CH3CN are studied in the gas phase by Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry. Sequential uptake of 4-6 acetonitrile molecules is observed for all metals. Rate constants show a weak dependence on both the metal and the number of acetonitrile molecules already in the cluster. Nanocalorimetry yields the enthalpy of the first reaction step. For most metals, this is consistent with a ligand exchange of water ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…46 Oxidation of Zn + (H 2 O) n to ZnOH + (H 2 O) m is also observed in the reactions with acetonitrile. 47 With 1-iodopropane, Zn + (H 2 O) n reacts efficiently to ZnI + (H 2 O) m , again with oxidation of the Zn centre. 48 These studies showed that hydrated monovalent zinc ions can be oxidized by suitable reactants, but the details of the reactions and their cluster size-dependence can be quite complex.…”
Section: Introductionmentioning
confidence: 99%
“…46 Oxidation of Zn + (H 2 O) n to ZnOH + (H 2 O) m is also observed in the reactions with acetonitrile. 47 With 1-iodopropane, Zn + (H 2 O) n reacts efficiently to ZnI + (H 2 O) m , again with oxidation of the Zn centre. 48 These studies showed that hydrated monovalent zinc ions can be oxidized by suitable reactants, but the details of the reactions and their cluster size-dependence can be quite complex.…”
Section: Introductionmentioning
confidence: 99%
“…32 They also explained the switch off for the hydrogen loss process for larger clusters due to the barrier increase when the solvated electron moves beyond the third solvation shell. 15 Our group has a long history in studying the reactivity of hydrated metal ions, 13,16,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] using Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) which is well suited for this task as it allows highest mass resolution coupled with long storage times to allow multiple collisions with reactant gases. In the present study, we couple the mass spectrometer with a tunable optical parametric oscillator (OPO)/amplifier system to conduct photodissociation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the second IE of zinc is even higher, and still Zn + (H 2 O) n are the most reactive species. The efficient ZnI + (H 2 O) m formation corresponds to the reactivity with acetonitrile, where Zn + (H 2 O) n is the only species for which hydroxide formation ZnOH + (H 2 O) m is observed …”
Section: Resultsmentioning
confidence: 99%
“…However, Zn­(I) cations are oxidized to Zn­(II), and a hydrogen atom is released upon uptake of a second HCl molecule . Monovalent hydrated zinc cations are also oxidized by acetonitrile in the gas phase . In studies of hydrated metal ions with small molecules like oxygen, nitrous oxide, carbon dioxide, and nitric oxide, different reactions depending on the metal and reactant were observed.…”
Section: Introductionmentioning
confidence: 99%